Analisis kebutuhan desain pembelajaran matematika berbasis konvensional untuk meningkatkan minat belajar siswa pada materi operasi matriks kelas xi - Syah, Muhammad Ferdian (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the need for conventional-based mathematics learning design to increase students' interest in learning Matrix Operations material for grade XI. The study was conducted at MAN 3 Jombang in January-February 2025 with research subjects involving 30 students from grades XI-7. The method used is descriptive qualitative which includes observation and interviews with mathematics teachers. The results of the observation showed that the majority of students were less interested in learning mathematics, considered mathematics difficult, and had difficulty understanding the concept of Matrix Operations. Interviews with teachers also revealed challenges in attracting students' attention and interest during learning. Therefore, this study suggests the need to adapt conventional learning designs to make them more interesting and interactive. An approach that involves discussions, question and answer sessions, and the use of real examples is expected to increase student engagement and their interest in learning mathematics.